Spanish International Pavilion, St. Loius, Mo. (St. Louis Color Postcard Co.)
The most outstanding building at the 1964-65 New York World's Fair. Presented to the city of St. Louis by the Spanish government. Fund for moving the building were raised by popular subscription.